PENGARUH MOTIVASI, KEDISIPLINAN DANKEPEMIMPINAN TERHADAP KINERJA SATUAN POLISI PAMONG PRAJA (SATPOL PP) DI KOTA PEKANBARU - Isjoni, M. Yogi Riantama; Indarti, Sri; Marzolina, Marzolina (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to identify and analyze the effect of motivation on Performance Civil ServicePolice Unit in the city of Pekanbaru. discipline influence on Performance Civil Service Police Unit inthe city of Pekanbaru. The influence of leadership Performance Civil Service Police Unit in Pekanbaru,and motivatian, discipline and leadership on performance Civil Service Police Unit Member inPekanbaru. Population is the total number of objects studied, the population in this study is themunicipal police Members of Pekanbaru. The number of population in this study were 140 municipalpolice Members with the status of Civil Servants. Given a population of only 140 people, it is feasiblefor sampling in the census.Data analysis and interpreting the data, the method used descriptive analysis and verification ofanalysis methods. Descriptive analysis method is used to describe the characteristics of respondentsand the research variables, whereas the verification method used to test the research hypotheses byusing relevant statistical tests. Whereas the verification method used in this study is multipleregression.The results showed that motivation influence on Performance Civil Service Police Unit in the city ofPekanbaru. Discipline influence on Performance Civil Service Police Unit in the city of Pekanbaru.Leadership effect on Performance Civil Service Police Unit in the city of Pekanbaru.Motivation,Discipline, Leadership effect on performance Civil Service Police Unit Member in Pekanbaru.